2021
DOI: 10.1302/2058-5241.6.210049
|View full text |Cite
|
Sign up to set email alerts
|

Reverse total shoulder arthroplasty (RTSA) versus open reduction and internal fixation (ORIF) for displaced three-part or four-part proximal humeral fractures: a systematic review and meta-analysis

Abstract: Despite rapid medical technology development, various challenges exist in three- and four-part proximal humeral fracture (PHF) management. This condition has led to a notably increased use of the reverse total shoulder arthroplasty (RTSA); however, open reduction and internal fixation (ORIF) is still the most widely performed procedure. Thus, these two modalities are crucial and require further discussion. We aim to compare the outcomes of three- or four-part PHF surgeries using ORIF and RTSA based on direct/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 59 publications
1
11
0
2
Order By: Relevance
“…When compared with hemiarthroplasty, RSA for treatment of proximal humeral fractures has been shown to have improved Constant scores, better active forward flexion, and better abduction [ 84 , 90 , 91 , 92 ].…”
Section: Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with hemiarthroplasty, RSA for treatment of proximal humeral fractures has been shown to have improved Constant scores, better active forward flexion, and better abduction [ 84 , 90 , 91 , 92 ].…”
Section: Surgical Approachmentioning
confidence: 99%
“…There have also been a number of studies and meta-analyses directly comparing RSA to ORIF and HA. Suroto et al found that RSA had lower rates of revision surgery, better forward flexion and abduction, and superior functional outcome measured by Constant Scores when compared with ORIF [ 91 ]. Perhaps the highest quality most recent study, the DelPhi study, demonstrated Constant scores that were 13.4 points higher in the RSA group than the ORIF group [ 92 ]; however the editors cautioned that follow-up was limited to two years [ 96 ].…”
Section: Surgical Approachmentioning
confidence: 99%
“…The literature has demonstrated that ORIF compared to rTSA for displaced three-part or four-part PHF has lower complication rates and higher revision rates. ORIF and rTSA were shown to be comparable in their ranges of motion [ 14 ]. Shoulder arthroplasty should be avoided in younger populations to prevent the need for revision arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was prepared for fasting from midnight, omitting the morning dose of OAD and insulin, and received low-molecular-weight heparin (LMWH) of 40 mg/12 h from the second day of pre-surgical. Successful ORIF procedure in the operating room was obtained [8] , [9] . On the 4th day post-surgery, the fasting blood glucose patient of 140 mg/dL, and she continue to received insulin aspart of 6–6–6 U, detemir of 8 U, metformin of 500 mg/12 h, acarbose 50 mg/8 h, and pioglitazone 30 mg/24 h, telmisartan 80 mg/24 h and bisoprolol 5 mg/24 h. The patient is planned to follow up in the internal and surgeon devision outpatient ward.…”
Section: Case Presentationmentioning
confidence: 99%